A review of multiproduct pipeline scheduling: from bibliometric analysis to research framework and future research directions - Li, Zhengbing; Liang, Yongtu; Liao, Qi; Zhang, Bo; Zhang, Haoran (Journal of Pipeline Science and Engineering, 2021)
Multiproduct pipelines play an important role in ensuring the downstream energy supply as they transport about 70% of refined products. To guarantee the safe and stable operation of pipelines during the scheduling horizon, it is necessary to make a reasonable schedule. During the past two decades, the multiproduct pipeline scheduling problem has been widely studied in the world. In this paper, the bibliometric analysis method is adopted to conduct quantitative analysis and visual research on related literature. Then, through the review of the existing articles, the research framework of multiproduct pipeline scheduling problem is constructed. Finally, the research defects and trends are analyzed. The aim of the paper is to provide a comprehensive understanding of multiproduct pipeline scheduling as well as some directions and inspiration for the future research.